The Role of Education Management In Information Systems, Accessibility of Education and Training In The Capacity Development of The State Civil Apparatus (ASN) - Fianita Dhany; Ali, Hapzi; Badarussyamsi, Badarussyamsi (Green Publisher, 2023)
The role of education management in information systems, training accessibility in increasing the capacity of the State Civil Apparatus (ASN) is a scientific literature review article. The purpose of writing this article is to build roles between variables that will be used in further research, within the scope of Human Resource Management and Leadership. The article writing method is the library research method , which is sourced from online media such as Google Scholar and other academic online media . Qualitative descriptive analysis. The results of this article are: 1) Information Systems have a role in education management in ASN Capacity Building; 2) Accessibility has a role in education management in ASN Capacity Building; 3) Education management plays a role in increasing ASN capacity.